PENGARUH KUALITAS PRODUK,HARGA,BRAND TRUST DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI CV MITRA MATRA MANDIRI PEKANBARU - Lewis Lewis; Silvia Sari Sitompul (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This study aims to determine: (1) the effect of significant sales growth on net profit margin (NPM) at PT Unilever, Tbk, (2) the effect of working capital turnover (WTC) at PT Unilevet, Tbk, and (3) the effect of Simultaneous growth in sales and working capital turnover (WTC) against net profit margin (NPM) at PT Unilever Tbk. This research is a type of associative research. The population of this study is the one used in this study, namely financial statement data and sales growth for 15 years with a research sample for 10 years from 2010 to 2019. The data analysis techniques used are normality test, multicolonierity test, autocorrelation test, heteroscedicity test. , multiple linear regression analysis, correlation analysis, coefficient of determination, significance test (t-statistical test) and simultaneous regression coefficient test (F test). The results showed that: The variable effect of sales growth obtained a significance value of 0.540> 0.05 and the t value - 0.644 <t table 2.365, meaning that sales growth did not have a significant effect on the Net Profit Margin (NPM), the first hypothesis was rejected. And the variable effect of working capital turnover above obtained a significance value of 0.773> 0.05 and a value of t count - 0.299 <t table 2.365, meaning that working capital turnover has no significant effect on Net Profit Margin (NPM), the second hypothesis is rejected. From the ANOVA test or F test, it is obtained a significance value of 0.782> 0.05 and a calculated F value of 0.254 <F table 4.46, which means that the turnover of working capital has no significant effect on the Net Profit Margin (NPM), the third hypothesis is rejected. Penggunaan genset saat ini menjadi sebuah kebutuhan penting bagi semua orang.Genset memiliki manfaat bagi setiap orang yaitu memberikan cadangan energi dalam keadaan darurat. Di CV Mitra Matra Mandiri terdapat merek genset yang di gunakan oleh konsumen yaitu merek Cummins dan Isuzu. Genset merupakan kebutuhan penting bagi masyarakat sehingga aktivitas kerja tidak terhambat oleh adaya pemadaman listrik baik di kantor maupun toko .Tujuan dari penelitian ini adalah untuk mengetahui pengaruh Kualitas Produk, Harga, Brand Trust dan kualitas pelayanan terhadap kepuasan konsumen di CV Mitra Matra Mandiri Pekanbaru. Populasi dalam penelitian ini adalah konsumen yang berbelaja di CV Mitra Matra Mandiri Pekanbaru.Pengambilan sampel pada penelitian ini menggunakan metode Accidental Sampling sehingga jumlah sampel penelitian ini adalah 120 responden.Teknik pengumpulan data melalui wawancara dan kuisioner. Hasil penelitian ini menunjukan bahwa Kualitas Produk berpengaruh signifikan terhadap Kepuasan Konsumen di CV Mitra Matra Mandiri Pekanbaru, Harga berpengaruh signifikan terhadap Kepuasan Konsumen di CV Mitra Matra Mandiri Pekanbaru. Brand Trust berpengaruh tidak signifikan terhadap Kepuasan Konsumen di CV Mitra Matra Mandiri Pekanbaru dan Kualitas Pelayanan berpengaruh tidak signifikan terhadap Kepuasan Konsumen di CV Mitra Matra Mandiri Pekanbaru.